1997
DOI: 10.1063/1.366232
|View full text |Cite
|
Sign up to set email alerts
|

Photo-illumination hardening of C60 crystals

Abstract: The effect of light on the hardness of C 60 crystals was investigated. The hardness increased after the crystals were illuminated with white light. Such a photo-illumination hardening was effective in a temperature range of 298-380 K. The photopolymerized C 60 molecules near the crystal surface were responsible for the hardening. The anomalous temperature dependence of the hardness at temperatures higher than 300 K, which we previously have observed, is explained as due to the photo-illumination hardening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…We have showed that the hardening of C 60 crystals is due to the interactions between dislocations and photoinduced products such as C 60 dimmers. 4,5 According to Rao and co-workers 12,13 such photoinduced polymerization can also occur for C 70 films. The cross section for photopolymerization of C 70 is, however, considerably smaller than that observed for C 60 .…”
Section: B Photoillumination Hardeningmentioning
confidence: 96%
See 2 more Smart Citations
“…We have showed that the hardening of C 60 crystals is due to the interactions between dislocations and photoinduced products such as C 60 dimmers. 4,5 According to Rao and co-workers 12,13 such photoinduced polymerization can also occur for C 70 films. The cross section for photopolymerization of C 70 is, however, considerably smaller than that observed for C 60 .…”
Section: B Photoillumination Hardeningmentioning
confidence: 96%
“…These results show that C 70 crystals also exhibit photoillumination hardening, similar to the observations in C 60 crystals. 4 When the magnitude ⌬H of the hardening is defined as the change in hardness due to the illumination for 50 h, the values of ⌬H at 300, 343, and 373 K are, respectively, 20, 61, and 43 MPa, as shown in Fig. 4.…”
Section: B Photoillumination Hardeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Photopolymerization of C 60 appears also in air (4)(5)(6). Light-irradiated in air C 60 becomes insoluble in common solvents, exhibits higher hardness compared to pristine fullerite and reverts to pristine fullerite after heat treatment at 400-500 K (4-7).…”
Section: Introductionmentioning
confidence: 98%
“…The aim of the present work was to investigate the wavelength dependence of phototransformation of C 60 single crystals in air using indentation hardness and dislocation mobility methods. The microindentation as a structure and depth sensitive test has been successfully used earlier in studies of the light-, atmosphere-, pressure and temperature-induced effects in fullerite (4,5,(7)(8)(9)(10)(11)(12). Investigations of the dislocation zone around indents can provide important information about photoinduced processes in the subsurface layer (7,11,13).…”
Section: Introductionmentioning
confidence: 98%